Interpretation of Ethical Considerations for the Inclusion of Patient-Reported Outcomes in Clinical Research (the PRO Ethics Guidelines) - ZHOU Hui, LIN Ying, ZHOU Guojin, TANG Kejing, YUAN Gang, YAO Mi (Zhongguo quanke yixue, 2023)
Patient-reported outcome (PRO) can provide evidence for medical decision making, health care policy development, and also serve as symptom parameters for condition monitoring to provide timely care targeting personal needs. With the widespread applications of PRO in clinical research, related ethical issues have received deeply attention. Published in 2022, the Ethical Considerations for the Inclusion of Patient-Reported Outcomes in Clinical Research (the PRO Ethics Guidelines) , is an important consensus-based reference developed for addressing ethical considerations of PRO in clinical research. Addressing ethical issues in PRO can improve the quality of PRO data while minimizing the risk, burden, and harm to participants and protecting the rights of participants and researchers. We interpreted the guideline, aiming to provide a guide for colleagues addressing ethical issues of PRO, and to increase their attention to these issues.